2009
DOI: 10.1136/thx.2008.108795
|View full text |Cite
|
Sign up to set email alerts
|

Is investigation of patients with haemoptysis and normal chest radiograph justified?

Abstract: Background:Haemoptysis is a common clinical symptom. A small proportion of patients present with haemoptysis and normal chest radiograph. The investigation strategy for this group of patients is unclear. The aim of this study is to see whether further investigations for this group of patients are justified.Methods:A retrospective analysis was conducted of consecutive patients presenting with haemoptysis and normal chest radiograph over a period of 56 months irrespective of their smoking status. These patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
53
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 15 publications
1
53
1
2
Order By: Relevance
“…In this series, there were 22 cases of lung cancer in 270 patients, reflecting a prevalence of lung cancer of 8.2% for this clinical scenario 1. Others have reported that the prevalence of lung cancer for this clinical scenario might be 5–6% 5.…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…In this series, there were 22 cases of lung cancer in 270 patients, reflecting a prevalence of lung cancer of 8.2% for this clinical scenario 1. Others have reported that the prevalence of lung cancer for this clinical scenario might be 5–6% 5.…”
mentioning
confidence: 53%
“…In this issue of Thorax ( see page ), Thirumaran and colleagues describe their experience with a consecutive group of patients evaluated for haemoptysis who had a normal chest radiograph 1. Over a 4-year period these investigators identified 270 patients who were evaluated for this problem.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4,[11][12][13] Other studies suggested that a greater awareness by the general population and family doctors of the signs and symptoms of LC could improve the prognosis of the disease, although the design of these studies does not allow definitive conclusions to be drawn on this.…”
mentioning
confidence: 99%
“…We read with interest the article by Thirumaran et al 1. They described their experience of 270 consecutive patients referred with haemoptysis and a normal chest radiograph.…”
mentioning
confidence: 99%